Diseño de un sistema SCADA para la adquisición de datos en medición de pérdidas primarias y secundarias en un sistema de flujo. - Belaño Rubio, Jefferson Vinicio (2022)
This work developed the design of the monitoring and data acquisition system for the measurement of primary head losses in pipes and secondary in fittings, consists of three sensors, two point sensors that allowed to measure the inlet and outlet pressure, a flow meter that determines the flow rate obtained at the outlet, we can manipulate the passage of flow through one of the seven different sections chosen which: three consist of pipes of different diameters and four of fittings; The measurements of the primary loss transmitters that measure the points in each of the three pipes obtained an error of 1% at maximum flow, as the flow decreases the error increases to 10% between the experimental data and the mathematical calculations, as the flow decreases (0.00038474 m3/s - 0.00009679 m3/s), the velocity of fluid (3.0372 m/s - 0.764 m/s), Re (41894.2894 - 11267.5599) and Δ (7108.4897 Pa - 615.7413 Pa) also, lambda (0.022 - 0.0302) increases at each flow reduction, the calculations in the secondary losses by accessories with varying flow decreases (0.00038594 m3/s - 0.00019799 m3/s), velocity of fluid (0.7617 m/s - 0.3907 m/s), Re (27582.1262 - 14620.2526) and Δ (57.6131 Pa - 15.1508 Pa) also, Epsilon has manufacturer's standard which is fixed, In the experimental values of epsilon (0.1476 - 0.0637) are variable pass through the point of regulation and not fixed as advertised by the manufacturers, it follows that the smaller the diameter of the pipe the higher losses will be obtained and the sensor measurements would be more accurate.